Applications of Artificial Intelligence and Smart Learning Methods for Children with Autism Spectrum Disorder: A Proposed Interactive Platform - Al-Hosan, Amani Mohammed; Alrajhi, Nada Abdulaziz (Journal of Ecohumanism, 2025)
Purpose:The current research aims to reveal the most important applications of artificial intelligence and smart learning methods for children with autism spectrum disorder (ASD) and early intervention from the perspectives of experts and specialists. Method: A total of (35) experts participated in the closed questionnaire related to the first two questions, and (7) specialists participated in the open-ended interview questions related to the third question. The psychometric properties of both tools (questionnaire and interview) were confirmed. Results: The results showed that the "Communication-Autistic" app and the "Card Talk" app were the most used by specialists and experts in early intervention. The "Autism in Saudi Arabia" app was the most used in the field of autism spectrum disorder. The results of applying the Rubric performance evaluation scale for smart components and applications in the proposed autism spectrum disorder platforms from the point of view of experts and specialists showed that the experts had positive comments and suggestions regarding the nature of the smart educational platform. Conclusion: This research emphasizes the importance of adopting, adapting, and launching the proposed educational platform based on artificial intelligence, as it took into account the achievements of existing platforms in this field, developing it, and taking into account the shortcomings and gaps in it by adding some tools, policies, and activities supported by systems for measuring the development of child learning with artificial intelligence